MODEL PEMBERDAYAAN MASYARAKAT “TAMAN EDUKASI REMPAH NUSANTARA” DALAM MEMANFAATKAN BAHAN ALAM DEDAUNAN REMPAH UNTUK PENGRAJIN ECOPRINT ENTERPRENEURSHIP DI DESA SILADO - Ine Kusuma Aryani; R. Beny Wijarnako Kertopati (Universitas Pahlawan Tuanku Tambusai, 2022)
This community service is through guidance and practice to open horizons of thinking and organize ecoprint art designs which are continuously fostered, trained where this ecoprint is a technique of providing beautiful, attractive and elegant motifs into cloth patterned with special leaves, namely leaves of Indonesian spices, In this national spice educational park, the ecoprint introduced, trained and developed is better known as the mordant sping botanical name and technique. Guidance and practice itself aims to provide motivation and innovation to the village community of Silado Kec. Donate to make a choice of community development models towards entrepreneurship or entrepreneurship, which are currently declining/sluggish in terms of income per capita as a home craftsman housewife, facing problems of difficulty paying mobile bank installments so it is necessary to provide a variety of entrepreneurial choices, by providing guidance and ecoprint practices with this mordan sping botanical makes the Silado village community motivated, open and develop entrepreneurship well. The results of this exploration of a more diverse mordant spring botanical technique can provide additional income and diverse insights about Indonesian traditional motifs that can be applied and developed which so far only feature simple herb leaf motifs that turn ordinary into extraordinary and elegant ones. which will eventually become a community development model that has a superior program in independent entrepreneurship for the people of Silado Village, Sumbang District. Model Pemberdayaan Masyarakat, Ecoprint, Enterpreneurship